Development of Antibacterial Resin Composites Containing a QAC-Based Monomer METAC. (2022) - Kohno, T.; Tsuboi, R.; Kitagawa, H.; Imazato, S.
Abstract : Purpose/Aim: It has been reported that an adhesive resin or resin sealants containing a quaternary ammonium compound (QAC)-based monomer 2-(methacryloyloxy)ethyl]trimethylammonium chloride (METAC) demonstrated contact inhibition of Streptococcus mutans on their surfaces. In this study, resin composites incorporating METAC was newly fabricated, and the antibacterial and anti-biofilm effects were evaluated by in vitro and in situ tests. Materials and Methods: An experimental resin composites (EX) was prepared by adding 6 wt% of METAC to a commercialized Bis-MEPP-based resin composites (GRACEFIL ZeroFlo, GC; GZ). To evaluate the antibacterial effects in vitro, 50 μL of S. mutans NTCT10449 or S. sobrinus ATCC 33478 suspension at 1.0 × 10^5 CFU/mL was inoculated on the disc-shaped cured specimen, and the number of viable bacteria was determined after 24 hours incubation by colony counting. To evaluate inhibitory effects against biofilm formation in situ, the specimens were fixed in the region of upper premolars and molars of 4 volunteers using a custom-made acrylic splint. The specimens were collected after 24 hours, and the biofilm formed on the surface was observed and analyzed by using a confocal laser scanning microscopy with LIVE/DEAD staining. GZ was used as a control. Results: For both S. mutans and S. sobrinus, the numbers of surviving cells on EX (mean values; 1.3 × 10^2 CFU and 2.3 × 10^2 CFU, respectively) were significantly smaller than those on GZ (mean values; 9.3 × 10^5 CFU and 4.0 × 10^4 CFU, respectively) (p < 0.05, Student's t-test, n = 3), and less than the initial bacterial amount (5.0 × 10^3 CFU). The thickness of biofilm formed in situ on EX (17.2 μm) was significantly smaller than that on GZ (30.5 μm) (p < 0.05, Students t-test, n = 4). Additionally, the volume fraction of bacteria with intact cell membrane in the biofilms formed on EX was 20% and significantly less than GZ which showed 67% (p < 0.05, Students t-test, n = 4). Conclusions: The newly fabricated resin composites containing the QAC-based antibacterial monomer METAC exhibited the bactericidal effects against oral bacteria on its surface. Moreover, due to such contact killing effects, the experimental composites could inhibit biofilm formation in the oral environment.